If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -8x + x = 3x + 11 Combine like terms: -1x + -8x = -9x -9x + x = 3x + 11 Combine like terms: -9x + x = -8x -8x = 3x + 11 Reorder the terms: -8x = 11 + 3x Solving -8x = 11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8x + -3x = 11 + 3x + -3x Combine like terms: -8x + -3x = -11x -11x = 11 + 3x + -3x Combine like terms: 3x + -3x = 0 -11x = 11 + 0 -11x = 11 Divide each side by '-11'. x = -1 Simplifying x = -1
| 4x^3-4y=0 | | 5x-6(14-4x)=32 | | y=x^2-2x+1 | | 2x+8=5x+77 | | 2x+8=5x | | 5x=-6x-9/3 | | (9n*n)=4+7n | | 2x-2y-2=0 | | Log(x)=1.3 | | logx=1.3 | | 2(x-1)=26.4 | | a^2+a-3a-3=0 | | ln(2x)=7 | | 2t^2-12t-25=0 | | -6+x=.6x-2.2+2 | | X+4=9+2x | | 35x-23=17 | | y=-5x+10 | | 0=6x+x^2+9 | | 7x-28=21 | | y=x+50 | | 3x+5=9x-(5-2x) | | x-(3x+1)=2x-(4x+3)-x | | 7p+12=13+6p | | 12-4x-x^2=36-16x^2+16 | | 2+10= | | -5.2x-3.3=22.7 | | 10y+2=7 | | 2*d=5d | | 4[-2(4x+3)+2(5x-5)]= | | 9y+(-3y-5)=4y-7 | | 2m(4m)= |